A Comparative Clinical Evaluation of Janu Basti with and Without Upnaha in Janu Sandhigata Vata (Osteoarthritis of Knee) - Kiran Kumain,; Ruchi Gupta,; Prabhat Kumar,; Ketan Mahajan, (International Journal of Ayurveda and Pharma Research, 2024)
Sandhigata Vata is the commonest form of musculoarticular disorder. It comes under eighty Nanatmaja Vata Vyadhi which mainly occurs due to Dhatukshaya in Vriddhavasta. Janu Sandhi is the major bearing joint in the body it’s more subjected to wear and tear. Sandhi comes under Madhayam Roga Marga where Vata gets localized in Sandhi thereafter Shleshaka Kapha Kshaya and cause symptoms like Shoola, Shotha, Akunchana Prasarana Vedana, Vatapurna Driti Sparsha which limits everyday activities such as walking, sitting and standing etc thus making patient disable to do daily activities. In the Shastras, Acharya Sushruta has firstly given the method of treatment such as Snehana, Upnaha, Agnikarma, Bandhana, Mardana. Upnaha is a type of Sagni and Niragni Swedana, which relieves stiffness, heaviness, cold and induces sweat. Janu Basti is type of Bahya Snehana and Swedana. It provides strength to the knee muscle, joints, and improves function of knee joint. In this study 50 patients having the complaints of osteoarthritis were randomly divided into 2 groups in Group A patients were treated with Janu Basti with Upnaha and in Group B were treated with only Janu Basti. The data shows that Janu Basti along with Upnaha i.e., group A has provided better relief in the disease of Sandhigata Vata.